A flexible self-supporting thin film electrode based on titanium oxide clusters and metal ion complexes modified MXene and its preparation method

By modifying MXene with titanium oxide clusters and metal ion complexes, the stacking problem of MXene nanosheets is solved, the electrochemical performance and mechanical flexibility are improved, and it is suitable for the energy storage needs of flexible electronic products.

CN119786272BActive Publication Date: 2025-09-12GUILIN UNIV OF ELECTRONIC TECH +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510043872.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-09-12
Estimated Expiration
2045-01-10

AI Technical Summary

Technical Problem

Existing MXene nanosheets are prone to stacking, which results in longer ion conduction paths and reduced electrochemical performance. In addition, they lack mechanical flexibility and are unable to meet the energy storage needs of flexible electronic products.

Method used

MXene is modified with titanium oxide clusters and metal ion complexes to form a stable MOF-type bond. Titanium oxide clusters are in situ grown on MXene nanosheets to form a multilayer structure and a three-dimensional network, which expands the interlayer spacing and increases the active sites.

Benefits of technology

The electrochemical performance and mechanical flexibility of MXene thin film electrodes are improved, making them suitable for flexible wearable electronic products, achieving fast charging and discharging and stable cycling performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786272B_ABST
    Figure CN119786272B_ABST
Patent Text Reader

Abstract

The present invention relates to a flexible self-supporting thin-film electrode based on MXene modified with titanium oxide clusters and metal ion complexes. The electrode is obtained by forming MXene nanosheet clusters through a mixed reaction of a MXene colloidal solution and a titanium oxide cluster precursor dispersion, and then doping the MXene nanosheet clusters into the MXene colloidal solution. The titanium oxide cluster precursor dispersion is obtained by a mixed reaction of Ti(OiPr)4, benzoic acid, and a metal ion dispersion. In the MXene nanosheet clusters, the titanium oxide clusters are in situ grown on the MXene nanosheets. The titanium oxide clusters are cage-like clusters. The present invention provides a type of MOF that can stably combine with MXene under acidic conditions, alleviating the problem of restacking of two-dimensional MXene nanosheets. It also provides more active sites to improve their electrochemical activity, thereby promoting the application of flexible thin-film electrodes in flexible wearable electronic products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of energy storage devices, and in particular to a flexible self-supporting thin film electrode based on MXene modified by titanium oxide clusters and metal ion complexes and a preparation method thereof. Background Art

[0002] As the practicality of flexible electronic products gains increasing attention, flexible supercapacitors have emerged to meet the energy storage needs of these products. They not only possess excellent flexibility but also enable rapid charge and discharge, and exhibit stable cycling performance, making them more suitable for everyday applications than traditional solid-state batteries. Flexible electrodes, the core components of flexible supercapacitors, significantly impact the performance of wearable and implantable electronic devices. These electrodes typically utilize novel materials, such as carbon nanotubes and graphene, to achieve higher energy storage capacity and faster charge and discharge rates.

[0003] MXene, a novel two-dimensional material composed of transition metal carbides, nitrides, or carbonitrides, shows broad application prospects in energy storage due to its excellent film-forming properties, electrical conductivity, tunable surface functional groups, and pseudocapacitive charge storage. However, MXene nanosheets often stack, which lengthens the ion conduction path and reduces their electrochemical performance. Furthermore, the mechanical flexibility of MXene nanosheets needs to be improved.

[0004] Therefore, a new MXene processing method is urgently needed to prepare a more stable and higher-performance MXene electrode to meet the needs of scientific and technological development. Summary of the Invention

[0005] Based on this, the present invention has developed a flexible, self-supporting thin-film electrode based on MXene modified with titanium oxide clusters and metal ion complexes, which exhibits excellent mechanical flexibility and electrochemical performance. The present invention provides a type of MOF that can stably bind to MXene in acidic conditions, alleviating the problem of restacking of two-dimensional MXene nanosheets while also providing more active sites, thereby improving their electrochemical activity.

[0006] One object of the present invention is to provide a flexible self-supporting thin film electrode based on MXene modified by titanium oxide clusters and metal ion complexes, wherein the flexible self-supporting thin film electrode based on MXene modified by titanium oxide clusters and metal ion complexes is obtained by mixing a MXene colloidal solution and a titanium oxide cluster precursor dispersion to form MXene nanosheet clusters, which are then doped into the MXene colloidal solution;

[0007] in,

[0008] The titanium oxide cluster precursor dispersion is obtained by mixing Ti(OiPr)4, benzoic acid and metal ion dispersion;

[0009] In the MXene nanosheet clusters, titanium oxide clusters are in situ grown on the MXene nanosheets;

[0010] The titanium oxide cluster is a cage-shaped cluster.

[0011] Furthermore, the flexible self-supporting thin film electrode based on MXene modified by titanium oxide clusters and metal ion complexes has a multilayer structure with an interlayer spacing ranging from 5.91 to 6.33 μm.

[0012] Furthermore, in the flexible self-supporting thin film electrode based on MXene modified by titanium oxide clusters and metal ion complexes, the doping percentage of MXene nanosheet clusters is 10%-40%.

[0013] Another object of the present invention is to provide a method for preparing the above-mentioned flexible self-supporting thin film electrode based on titanium oxide clusters and metal ion complexes modified MXene, comprising the following steps:

[0014] S1. Place the MAX raw material in an acid solution for etching, wash it to neutrality, and then use an intercalation agent for intercalation to separate and obtain a MXene colloidal solution;

[0015] S2, mixing Ti(OiPr)4, benzoic acid, metal ion dispersion and solvent, and reacting to obtain a titanium oxide cluster precursor dispersion;

[0016] S3, blending the MXene colloid solution and the titanium oxide cluster precursor dispersion, and performing a hydrothermal reaction under an inert atmosphere, purifying, washing, and drying to obtain MXene nanosheet clusters;

[0017] S4. The MXene nanosheet clusters are doped into the MXene colloidal solution by stirring, purified, and dried to obtain the flexible self-supporting thin film electrode based on the titanium oxide cluster and metal ion complex modified MXene.

[0018] Further, the chemical formula of the MAX raw material is MAX;

[0019] in,

[0020] The M is selected from at least one of Ti, V, Nb, Mo, Zr, Cr or Hf;

[0021] The A is selected from at least one of Al, Ga, Si, Ti, Sn or Ge;

[0022] The X is selected from at least one of C and N.

[0023] Furthermore, the acid solution is a mixed solution of HCl and HF.

[0024] Furthermore, the intercalant is lithium chloride.

[0025] Furthermore, in the titanium oxide cluster precursor dispersion, the structural formula of the titanium oxide cluster precursor is Ti8M2BA 16 , forming a cage-like cluster;

[0026] in,

[0027] The M is a metal ion;

[0028] The BA is a benzoate ligand.

[0029] Furthermore, the metal ions are selected from one or more of lanthanides, actinides or transition metals.

[0030] Furthermore, in step S3, the solute mass ratio of the MXene colloidal solution to the metal ion dispersion is 1:0.5-1:5.

[0031] Furthermore, in step S4, the mass ratio of the MXene colloidal solution to the MXene nanosheet clusters is 1:0.1-1:0.65;

[0032] The concentration of the MXene colloid solution is 3-30 mg·mL -1 .

[0033] Furthermore, the hydrothermal reaction temperature is 80-150° C., and the insulation time is 48-72 hours.

[0034] Another object of the present invention is to provide the application of the above-mentioned flexible self-supporting thin film electrode based on titanium oxide clusters and metal ion complexes modified MXene in energy storage devices.

[0035] The present invention has the following beneficial effects:

[0036] The present invention provides a flexible self-supporting thin film electrode based on MXene modified by titanium oxide clusters and metal ion complexes. The titanium oxide clusters and metal ions form a type of MOF that can stably bind to MXene under acidic conditions, alleviating the problem of two-dimensional MXene nanosheets restacking, while also providing more active sites to improve their electrochemical activity. On the one hand, the titanium oxide clusters are cage-like clusters that stretch the distance between MXene nanosheets, expand the interlayer spacing, facilitate ion transport, and improve electrochemical performance. On the other hand, the MXene sheets are connected by the clusters to form a three-dimensional network structure. When subjected to external forces, the MXene sheets interact with each other, reducing stress concentration, thereby improving the mechanical flexibility of the thin film electrode and promoting the application of flexible thin film electrodes in flexible wearable electronic products. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 The electrochemical performance test diagram of the thin film electrodes prepared in Examples 1-4 and Comparative Examples 1-3 in a Swagelok battery is shown;

[0038] in,

[0039] Figure 1 (a) shows the -1 CV curves of Examples 1-4 and Comparative Examples 1-3 at different scanning rates;

[0040] Figure 1 (b) shows the -1 GCD curves of Examples 1-4 and Comparative Examples 1-3 at different scanning rates.

[0041] Figure 2 Macroscopic photographs of the flexible self-supporting thin film electrode based on titanium oxide clusters and metal ion complex-modified MXene prepared in Example 2 are shown in a bent state, a folded state, after filtration and drying, and under vertical load;

[0042] in,

[0043] Figure 2 (a) shows a macroscopic photograph in a bent state;

[0044] Figure 2 (b) shows a macroscopic photograph of the folded state;

[0045] Figure 2 (c) shows a macroscopic photograph after filtration and drying;

[0046] Figure 2 (d) shows a macroscopic photograph under vertical load.

[0047] Figure 3The XRD comparison diagram of the flexible self-supporting thin film electrode based on titanium oxide clusters and metal ion complex modified MXene prepared in Example 2 and the MXene thin film electrode prepared in Comparative Example 3 is shown;

[0048] in,

[0049] Figure 3 (a) shows the XRD pattern of the MXene thin film electrode prepared in Comparative Example 3;

[0050] Figure 3 (b) shows the XRD pattern of the flexible self-supporting thin film electrode based on titanium oxide clusters and metal ion complex modified MXene prepared in Example 2.

[0051] Figure 4 Scanning electron microscope (SEM) images of a flexible self-supporting thin film electrode based on titanium oxide clusters and metal ion complex-modified MXene prepared in Example 2 and a MXene thin film electrode prepared in Comparative Example 3 are shown;

[0052] in,

[0053] Figure 4 (a) shows a cross-sectional view of MXene;

[0054] Figure 4 (b) shows the MXene surface image;

[0055] Figure 4 (c) shows the cross-sectional view of the MXene / Ti-O-La cluster;

[0056] Figure 4 (d) shows the surface image of MXene / Ti-O-La clusters. DETAILED DESCRIPTION

[0057] In order to more clearly illustrate the technical solutions of the present invention, the following examples are given. Unless otherwise stated, the raw materials, reactions and post-processing methods mentioned in the examples are common raw materials on the market and technical methods well known to those skilled in the art.

[0058] The terms "preferred," "preferably," "more preferred," and the like, used herein, refer to embodiments of the invention that may provide certain benefits under certain circumstances. However, other embodiments may also be preferred under the same or other circumstances. Furthermore, the recitation of one or more preferred embodiments does not imply that other embodiments are not useful, nor is it intended to exclude other embodiments from the scope of the invention.

[0059] It should be understood that, except in any operating examples, or where otherwise indicated, all numbers expressing, for example, quantities of ingredients used in the specification and claims are to be understood as being modified in all instances by the term "about." Accordingly, unless indicated to the contrary, the numerical parameters set forth in the following specification and appended claims are approximations that may vary depending upon the desired properties to be obtained by the present invention.

[0060] The filter membrane in the embodiment of the present invention is a cellulose water filter membrane with a pore size of 0.45 μm, purchased from Shanghai Xingya Purification Material Factory

[0061] The water in the embodiments of the present invention is all deionized water.

[0062] Example 1

[0063] A flexible self-supporting thin film electrode based on MXene modified with titanium oxide clusters and metal ion complexes, obtained by mixing a MXene colloidal solution and a titanium oxide cluster precursor dispersion to form MXene nanosheet clusters, which are then doped into the MXene colloidal solution;

[0064] in,

[0065] The titanium oxide cluster precursor dispersion is obtained by mixing Ti(OiPr)4, benzoic acid and lanthanum chloride aqueous solution;

[0066] In the MXene nanosheet clusters, titanium oxide clusters are in situ grown on the MXene nanosheets;

[0067] The titanium oxide cluster is a cage-shaped cluster.

[0068] The method for preparing the flexible self-supporting thin film electrode based on titanium oxide clusters and metal ion complex modified MXene comprises the following steps:

[0069] S1. At room temperature, measure 1ml HF, 2ml H2O, and 7ml HCl into a polytetrafluoroethylene reaction bottle and stir for 5 minutes to mix evenly. Weigh 0.5g of Ti3AlC2 MAX phase with excess Al (the molar ratio of each element in the MAX phase is Ti:C:Al=2:1.25:2.2, here the Ti3AlC2 MAX phase with excess Al is referred to as Al-Ti3AlC2, the same below) and add it to the mixed solution. Stir in a water bath at 40°C for 36h at a speed of 400r / min for etching. The resulting etched product is repeatedly centrifuged and washed until neutral. After centrifugation, the lower layer is precipitated to form a multilayer MXene. Weigh 0.5g of LiCl and stir and dissolve it in 25ml of water to prepare a LiCl solution. Transfer the multilayer MXene to the LiCl solution and magnetically stir for 24h at a speed of 400r / min. The mixture was then transferred to a centrifuge tube and centrifuged until the upper dispersion turned black and the lower precipitate expanded. Ultrasonic treatment was performed for 30 minutes, followed by centrifugation at 1500 rpm for 20 minutes. The upper dispersion was then taken and centrifuged at 3500 rpm for 15 minutes to obtain a MXene colloidal solution. 2 ml of the MXene colloidal solution was taken, vacuum filtered, dried, and the film was peeled off to determine the concentration of the colloidal solution (typically, the concentration of the MXene colloidal solution prepared from 0.5 g of Al-Ti3AlC2 is approximately 10 mg / ml).

[0070] S2, prepare a 10 mg / ml lanthanum chloride aqueous solution with deionized water, dissolve 0.61 ml of Ti(OiPr)4, 1.22 g of benzoic acid and 8 ml of the lanthanum chloride aqueous solution in 6 ml of acetonitrile, and sonicate for 0.5 h to form a titanium oxide cluster precursor dispersion;

[0071] S3. The titanium oxide cluster precursor dispersion was mixed with 20 mg of MXene colloidal solution, stirred to mix evenly, and then subjected to hydrothermal reaction under nitrogen protection. After the reaction was kept at 100° C. for 72 hours, the mixture was naturally cooled to room temperature, centrifuged at 3500 r / min for 5 minutes, washed multiple times to remove acetonitrile, and then dried to obtain powdered MXene nanosheet clusters loaded with titanium oxide clusters and lanthanum metal ion complexes;

[0072] S4. Dissolve 50 mg of the MXene nanosheet clusters in 10 ml of water to prepare a 5 mg / ml Ti-O-La cluster dispersion. Take 1 ml of the Ti-O-La cluster dispersion, mix and stir it with 20 mg of MXene colloidal solution, and then vacuum filter it with a 0.45 μm cellulose aqueous filter membrane. Vacuum dry it at room temperature for 4 hours to obtain a flexible self-supporting thin film electrode based on MXene modified by titanium oxide clusters and metal ion complexes.

[0073] Example 2

[0074] A flexible self-supporting thin film electrode based on MXene modified with titanium oxide clusters and metal ion complexes, obtained by mixing a MXene colloidal solution and a titanium oxide cluster precursor dispersion to form MXene nanosheet clusters, which are then doped into the MXene colloidal solution;

[0075] in,

[0076] The titanium oxide cluster precursor dispersion is obtained by mixing Ti(OiPr)4, benzoic acid and lanthanum chloride aqueous solution;

[0077] In the MXene nanosheet clusters, titanium oxide clusters are in situ grown on the MXene nanosheets;

[0078] The titanium oxide cluster is a cage-shaped cluster.

[0079] The preparation method of this embodiment is different from that of Example 1 in that, in step S4, 60 mg of the MXene nanosheet clusters are dissolved in 10 ml of water to prepare a 6 mg / ml Ti-O-La cluster dispersion. The rest of the preparation method is the same as that of Example 1.

[0080] Example 3

[0081] A flexible self-supporting thin film electrode based on MXene modified with titanium oxide clusters and metal ion complexes, obtained by mixing a MXene colloidal solution and a titanium oxide cluster precursor dispersion to form MXene nanosheet clusters, which are then doped into the MXene colloidal solution;

[0082] in,

[0083] The titanium oxide cluster precursor dispersion is obtained by mixing Ti(OiPr)4, benzoic acid and lanthanum chloride aqueous solution;

[0084] In the MXene nanosheet clusters, titanium oxide clusters are in situ grown on the MXene nanosheets;

[0085] The titanium oxide cluster is a cage-shaped cluster.

[0086] The preparation method of this embodiment is different from that of Example 1 in that, in step S4, 70 mg of the MXene nanosheet clusters are dissolved in 10 ml of water to prepare a 7 mg / ml Ti-O-La cluster dispersion. The rest of the preparation method is the same as that of Example 1.

[0087] Example 4

[0088] A flexible self-supporting thin film electrode based on MXene modified with titanium oxide clusters and metal ion complexes, obtained by mixing a MXene colloidal solution and a titanium oxide cluster precursor dispersion to form MXene nanosheet clusters, which are then doped into the MXene colloidal solution;

[0089] in,

[0090] The titanium oxide cluster precursor dispersion is obtained by mixing Ti(OiPr)4, benzoic acid and cerium chloride aqueous solution;

[0091] In the MXene nanosheet clusters, titanium oxide clusters are in situ grown on the MXene nanosheets;

[0092] The titanium oxide cluster is a cage-shaped cluster.

[0093] The preparation method of this embodiment differs from that of Example 1 in that, in step S2, the lanthanum chloride aqueous solution is replaced with a cerium chloride aqueous solution of the same concentration; in step S4, 60 mg of the MXene nanosheet clusters are dissolved in 10 ml of water to prepare a 6 mg / ml Ti-O-Ce cluster dispersion. The rest of the preparation method is the same as that of Example 1.

[0094] Comparative Example 1

[0095] A MXene thin film electrode is prepared from a MXene colloidal solution. The preparation method comprises the following steps:

[0096] S1. Prepare a MXene colloidal solution, the preparation method of which is the same as that in Example 1;

[0097] S2. Take 2 ml of the MXene colloidal solution, vacuum filter it with a filter membrane, and vacuum dry it at room temperature for 4 hours to obtain the MXene thin film electrode.

[0098] Comparative Example 2

[0099] A MXene thin film electrode is prepared by hydrothermal reaction of a MXene colloidal solution. The preparation method comprises the following steps:

[0100] S1. Prepare a MXene colloidal solution, the preparation method of which is the same as that in Example 1;

[0101] S2. The MXene colloidal solution is subjected to a hydrothermal reaction under nitrogen protection. After the reaction is kept at 100° C. in a vacuum oven for 72 hours, it is naturally cooled to room temperature. The resulting product is vacuum filtered with a filter membrane and vacuum dried at room temperature for 4 hours to obtain the MXene thin film electrode.

[0102] Comparative Example 3

[0103] A MXene thin film electrode is obtained by mixing a MXene colloidal solution and a titanium oxide cluster precursor dispersion to form MXene nanosheet clusters, which are then doped into the MXene colloidal solution.

[0104] The difference between the preparation method of the MXene thin film electrode and that of Example 1 is that in step S2, no lanthanum chloride aqueous solution is added, and the rest of the preparation method is the same as that of Example 1.

[0105] Test Case

[0106] The thin film electrodes prepared in Examples 1-4 and Comparative Examples 1-3 were tested. Unless otherwise specified, the test methods adopted were all conventional test methods used by those skilled in the art.

[0107] Test method:

[0108] (1) The thin film electrodes prepared in Examples 1-4 and Comparative Examples 1-3 were subjected to electrochemical performance tests in a Swagelok cell.

[0109] (2) The thin film electrodes prepared in Examples 1-4 and Comparative Examples 1-3 were directly used as working electrodes, activated carbon was used as counter electrode, and Ag / AgCl was used as reference electrode to construct a three-electrode system. (a) Cv and (b) GCD tests were performed in 3M H2SO4 electrolyte. -1 and 1A·g -1 Test the specific capacitance.

[0110] The test results are as follows Figure 1 and as shown in Table 1.

[0111] Figure 1 The electrochemical performance test diagram of the thin film electrodes prepared in Examples 1-4 and Comparative Examples 1-3 in a Swagelok battery is shown;

[0112] in,

[0113] Figure 1 (a) shows the -1 CV curves of Examples 1-4 and Comparative Examples 1-3 at different scanning rates;

[0114] Figure 1 (b) shows the -1 GCD curves of Examples 1-4 and Comparative Examples 1-3 at different scanning rates.

[0115] Table 1 Specific capacitance test results

[0116]

[0117]

[0118] Depend on Figure 1 As shown in Table 1, compared with Comparative Example 1, the electrochemical performance of Comparative Example 2 is improved after hydrothermal treatment. Compared with Comparative Example 2, the electrochemical performance of the thin film electrode of Comparative Example 3 is further improved by loading titanium oxide clusters. As can be seen from Examples 1-4, after the metal ions coordinate the titanium oxide clusters to form a three-dimensional network structure, the electrochemical performance of the thin film electrode is greatly improved. Among them, the electrochemical performance of the thin film electrode of Example 2 coordinated with 6 mg / ml lanthanum ion dispersion is the best, and the specific capacitance measured in 3M H2SO4 electrolyte reaches 660F·g -1 .

[0119] Figure 2 Macroscopic photographs of the flexible self-supporting thin film electrode based on titanium oxide clusters and metal ion complex-modified MXene prepared in Example 2 are shown in a bent state, a folded state, after filtration and drying, and under vertical load;

[0120] in,

[0121] Figure 2 (a) shows a macroscopic photograph in a bent state;

[0122] Figure 2 (b) shows a macroscopic photograph of the folded state;

[0123] Figure 2 (c) shows a macroscopic photograph after filtration and drying;

[0124] Figure 2 (d) shows a macroscopic photograph under vertical load.

[0125] Depend on Figure 2 It can be seen that the composite thin film electrode can be obtained by vacuum filtration, can be rolled and bent without breaking, has a certain load capacity, and exhibits excellent mechanical flexibility.

[0126] Figure 3 The XRD comparison diagram of the flexible self-supporting thin film electrode based on titanium oxide clusters and metal ion complex modified MXene prepared in Example 2 and the MXene thin film electrode prepared in Comparative Example 3 is shown;

[0127] in,

[0128] Figure 3 (a) shows the XRD pattern of the MXene thin film electrode prepared in Comparative Example 3;

[0129] Figure 3 (b) shows the XRD pattern of the flexible self-supporting thin film electrode based on titanium oxide clusters and metal ion complex modified MXene prepared in Example 2.

[0130] Depend on Figure 3 It can be seen that Figure 3 In (b), different Figure 3 The peaks of (a) were analyzed and compared, indicating that the MXene film loaded with titanium oxide clusters and lanthanum metal ion complexes was successfully synthesized.

[0131] Figure 4 Scanning electron microscope (SEM) images of a flexible self-supporting thin film electrode based on titanium oxide clusters and metal ion complex-modified MXene prepared in Example 2 and a MXene thin film electrode prepared in Comparative Example 3 are shown;

[0132] in,

[0133] Figure 4 (a) shows a cross-sectional view of MXene;

[0134] Figure 4 (b) shows the MXene surface image;

[0135] Figure 4 (c) shows the cross-sectional view of the MXene / Ti-O-La cluster;

[0136] Figure 4 (d) shows the surface image of MXene / Ti-O-La clusters.

[0137] Figure 4 The SEM cross-sectional image shows that the MOF structure formed by titanium oxide clusters and lanthanum metal ion complexes is effectively inserted into the interlayer of MXene nanosheets, which expands the interlayer spacing and facilitates the transport of ions. The SEM surface image clearly shows that the MXene nanosheets have adsorbed a large number of titanium oxide clusters and lanthanum metal ion complex particles, effectively improving the electrochemical performance of the thin film electrode.

[0138] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the invention can be embodied in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as illustrative and non-restrictive, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations that come within the meaning and range of equivalents of the claims be embraced therein.

[0139] In addition, it should be understood that although this specification is described in terms of implementation methods, not every implementation method contains only one independent technical solution. This narrative method of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other implementation methods that can be understood by those skilled in the art.

Claims

1. A flexible self-supporting thin film electrode based on MXene modified with titanium oxide clusters and metal ion complexes, characterized in that: The flexible self-supporting thin film electrode based on MXene modified by titanium oxide clusters and metal ion complexes is obtained by mixing a MXene colloidal solution and a titanium oxide cluster precursor dispersion to form MXene nanosheet clusters, which are then doped into the MXene colloidal solution; in, The titanium oxide cluster precursor dispersion is obtained by mixing Ti(OiPr)4, benzoic acid and metal ion dispersion; In the MXene nanosheet clusters, titanium oxide clusters are in situ grown on the MXene nanosheets; The titanium oxide cluster is a cage-like cluster; The flexible self-supporting thin film electrode based on MXene modified by titanium oxide clusters and metal ion complexes has a multilayer structure with an interlayer spacing range of 5.91-6.33 μm; The metal ion dispersion includes metal ions, and the metal ions are selected from one or more of lanthanide, actinide or transition metals.

2. The flexible self-supporting thin film electrode based on MXene modified by titanium oxide clusters and metal ion complexes according to claim 1, characterized in that: In the flexible self-supporting thin film electrode based on MXene modified by titanium oxide clusters and metal ion complexes, the doping percentage of MXene nanosheet clusters is 10%-40%.

3. The method for preparing a flexible self-supporting thin film electrode based on MXene modified with titanium oxide clusters and metal ion complexes according to any one of claims 1 to 2, characterized in that: The steps include: S1. Place the MAX raw material in an acid solution for etching, wash it to neutrality, and then use an intercalation agent for intercalation to separate and obtain a MXene colloidal solution; S2, mixing Ti(OiPr)4, benzoic acid, metal ion dispersion and solvent, and reacting to obtain a titanium oxide cluster precursor dispersion; S3, blending the MXene colloid solution and the titanium oxide cluster precursor dispersion, and performing a hydrothermal reaction under an inert atmosphere, purifying, washing, and drying to obtain MXene nanosheet clusters; S4, doping the MXene nanosheet clusters into the MXene colloidal solution by stirring, purifying, and drying to obtain the flexible self-supporting thin film electrode based on the titanium oxide cluster and metal ion complex modified MXene; The chemical formula of the MAX raw material is MAX; in, The M is selected from at least one of Ti, V, Nb, Mo, Zr, Cr or Hf; The A is selected from at least one of Al, Ga, Si, Ti, Sn or Ge; The X is selected from at least one of C and N.

4. The method for preparing a flexible self-supporting thin film electrode based on MXene modified with titanium oxide clusters and metal ion complexes according to claim 3, characterized in that: In the titanium oxide cluster precursor dispersion, the structural formula of the titanium oxide cluster precursor is Ti8M2BA 16 ; in, The M is a metal ion; The BA is a benzoate ligand.

5. The method for preparing a flexible self-supporting thin film electrode based on MXene modified with titanium oxide clusters and metal ion complexes according to claim 4, characterized in that: The metal ions are selected from one or more of lanthanide, actinide or transition metals.

6. The method for preparing a flexible self-supporting thin film electrode based on MXene modified with titanium oxide clusters and metal ion complexes according to claim 3, characterized in that: In step S4, the mass ratio of the MXene colloidal solution to the MXene nanosheet clusters is 1:0.1-1:0.65; The concentration of the MXene colloid solution is 3-30 mg·mL -1 .

7. The method for preparing a flexible self-supporting thin film electrode based on MXene modified with titanium oxide clusters and metal ion complexes according to claim 3, characterized in that: The hydrothermal reaction temperature is 80-150° C., and the insulation time is 48-72 hours.

8. Use of the flexible self-supporting thin film electrode based on MXene modified with titanium oxide clusters and metal ion complexes according to any one of claims 1-2 in energy storage devices.

Citation Information

Patent Citations

  • MXene loaded noble metal cluster catalyst as well as preparation method and application thereof

    CN113235108A

  • Method for preparing titanium-based metal organic framework membrane from titanium oxide clusters

    CN115245764A